PENGEMBANGAN MODUL KESIAPSIAGAAN BENCANA ANGIN PUTING BELIUNG UNTUK MAHASISWA PENDIDIKAN GEOGRAFI UNNES - Iryanthony, Sigit Bayhu (Universitas Negeri Semarang, 2015)
Angin puting beliung is a disaster which frequently happens in Indonesia. Based on National Agency ofDisaster Management (BNPB) data, it contributed 21% of all disasters in Indonesia. This study aimed todetermine appropriate learning modules to recognize angin puting beliung by utilizing maritimemeteorological information from BMKG and to determine students cognitive level in learning andunderstanding maritime meteorological information data from BMKG by using the developed module.Research conducted on Geography Education students UNNES. The method used in this research wasresearch and development (Research and Development). The research process started with a preparatorystudy, media arrangement, media validation by media and material experts. The modul feasibility wasdecalred as very feasible with average value of 78.58. The results showed that there were cognitive levelincreasement of 1st, 5th, and 7th semester Students at 29.5 (out of range 0-100). More significant improvementoccurred in the 7th semester students at 38.4 (out of range 0-100). Hence, this module feasible and proven toimprove learning outcomes of Geography Education Students of UNNES.